Phytochemical Analysis of Tinospora Cordifolia by Gc-Ms and Evaluation of its Antiurolithiatic Potential by In Siilico - Sowmya. M; Ramesh. S; Ganne Venkata Sudhakar Rao; Ramesh. S; Jalantha. P; Sujatha. P. L; Indumathi. R (The Indian Veterinary Journal, 2024)
Urolithiasis is the third most common urinary tract disorder affecting both men and women with an estimated global frequency of approximately 14%. Ethylene glycol is a lithiatic agent which is a potent component for experimental induction of urolithiasis. The enzymes like glycolate oxidase, oxalate oxidase are employed in oxalate metabolism which involve in caliculi formation. CD44 is a receptor of the stone modulating protein, Osteopontin (OPN). Tinospora cordifolia is a medicinal plant distributed throughout the Indian subcontinent, and contains many phytochemicals used for various ailments. GC-MS and ADME analysis were done and active principles (ligands) were selected. The protein and ligand structures were prepared and molecular docking was done in Autodoc Vina. 2D and 3D structures were generated by Discovery Studio Visualizer. The molecular interaction revealed that the phytochemical Columbin has greater binding activity against all three proteins namely glycolate oxidase, oxalate oxidase and CD44. Khellin, Valerenic acid and Capsazepine showed moderate binding activity against these targets. Thus, Tinospora cordifolia is found to exhibit significant antiurolithiatic activity through molecular interaction by in silico.